Optimalisasi Profitabilitas melalui Integrasi Supply Chain Management dan Enterprise Resource Planning: Studi Kasus PT. Unilever Indonesia - Marpaung, Shyndy Shyntia; Simanjuntak, Mariana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
In an era of increasingly tight global competition, companies are required to continueto increase their profitability and operational efficiency. One approach that can help companies achieve this goal is through effective supply chain management and the implementation of an integrated Enterprise Resource Planning (ERP) system. This research aims to analyze how the implementation of SCM and ERP can increase company profitability, especially in the context of PT. Unilever Indonesia. The focus of this research is to understand how the integration of SCM and ERP systems can help companies optimize their supply chains, increase operational efficiency, and ultimately increase company profits. The research method used in this research is literature study and data analysis. The research results show that the implementation of SCM and ERP at PT. Unilever Indonesia has provided significant benefits in increasing operational efficiency, optimizing supply chains, and increasing company profitability. The integration of SCM and ERP systems allows companies to have better visibility over their entire business processes, speed up decision making, and increase responsiveness to market changes.